Pengoptimuman parameter penuangan untuk aloi magnesium (Mg) sebagai anod korbanan bagi kegunaan bawah tanah - Hazrin Jahidi Jaafar (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
In this study, optimization of casting parameter on Mg alloys for underground sacrificial anodes are the main targets in making high efficiency anodes.